Distribution Of Batillaria Zonalis (Mollusca : Gastropoda) on Avicennia Marina (Forsk.) Vierh In The Coast Of Banggi, Rembang, Central Java - Dafit Ariyanto Ariyanto; Dietriech Geoffrey Bengen; Tri Prartono; Yusli Wardiatno (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2018)
Mangroves prove a habitat for Batillaria zonalis as nursery ground, feeding ground and reproductive ground. This research was conducted from September 2016 - August 2017 and to determine the spasial and temporal pattern with based on mangrove zone and environmental characteristics. The gastropods and environmental characteristics were analyzed using Principal Component Analysis (PCA). The results showed that significant changes in gastropod assemblages were primarily due to changes in the water quality and season. Correlation between gastropod and physico-chemical parameters in A. marina revealed significant relationship with gastropod B. zonalis distribution.